THE REFLECTION OF THE LEXICON OF ORAL SPEECH IN CONTEMPORARY FRENCH WORKS OF ART IN THE TRANSLATION INTO UZBEK - Radjabova Maftuna Bakhromovna (Scholar Express Journal, 2025)
This article examines the challenges and strategies involved in translating colloquial language from contemporary French literature into Uzbek. Contemporary French fiction often utilizes a wide range of informal expressions, including regional dialects, slang, familiar phrases, and even vulgarisms, to create realistic and stylistically vibrant narratives. The translation of these elements presents significant difficulties due to cultural and linguistic differences between French and Uzbek. The study analyzes specific examples of colloquialisms and explores various translation techniques, such as cultural adaptation, paraphrasing, and the use of explanatory notes, to determine the most effective approaches for conveying the nuances of the original text while maintaining its impact and accessibility for the Uzbek reader. The paper ultimately highlights the complex interplay between linguistic accuracy and cultural appropriateness in literary translation.
Keywords: Contemporary French literature; colloquial language; translation